New Zealand Maori: The Quest for Indigenous Autonomy. Issue 1 (1st January 2016) - Hill, Richard S.
Abstract: The indigenous Maori of New Zealand, like their counterparts in other jurisdictions, express a holistic inseparability from the land: they are tangata whenua, 'people of the land'. But most of their land had been lost to the colonisers by 1900, and only a small proportion of it has been returned through reparational negotiations between tribes and governments over the last 25 years. These negotiations have mostly now been concluded, and thus there is no prospect of the return of significant land areas in the foreseeable future. Moreover, these areas have been transferred to tribes as land, unaccompanied by constitutional concessions in such areas as governance, law and policing; and in any case, most Maori now live in urban areas, far from their tribal homelands. From the Maori perspective, however, the negotiations have been overarched by a quest to restore that which was promised in the nation's foundational Treaty of Waitangi in 1840—their rangatiratanga, loosely translatable as autonomy. The article examines the prospects for self-determination within contexts of tribal landlessness and mass urbanisation. It explores ways in which tribal leaderships are in the process of forging forms of autonomy which, while non-territorial, are meaningful to the tangata whenua precisely because of indigenous understandings of the concepts of tangata, whenua and rangatiratanga .